Rational design and synthesis of 2-(1H-indazol-6-yl)-1H-benzo[d]imidazole derivatives as inhibitors targeting FMS-like tyrosine kinase 3 (FLT3) and its mutants. (31st December 2022) - Im, Daseul; Jun, Joonhong; Baek, Jihyun; Kim, Haejin; Kang, Dahyun; Bae, Hyunah; Cho, Hyunwook; Hah, Jung-Mi
Abstract: Fms-like tyrosine kinase 3 (FLT3) has been verified as a therapeutic target for acute myeloid leukaemia (AML). In this study, we report a series of 2-(1 H -indazol-6-yl)-1 H -benzo[d]imidazol-5-yl benzamide and phenyl urea derivatives as potent FLT3 inhibitors based on the structural optimisation of previous FLT3 inhibitors. Derivatives were synthesised as benzamide 8a –k, 8n –z, and phenyl urea 8l –m, with various substituents. The most potent inhibitor, 8r, demonstrated strong inhibitory activity against FLT3 and FLT3 mutants with a nanomolar IC50 and high selectivity profiles over 42 protein kinases. In addition, these type II FLT3 inhibitors were more potent against FLT3 mutants correlated with drug resistance. Overall, we provide a theoretical basis for the structural optimisation of novel benzimidazole analogues to develop strong inhibitors against FLT3 mutants for AML therapeutics.